2021
DOI: 10.1111/tpj.15591
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal responses in grapevine become increasingly more tolerant to low water potentials throughout the growing season

Abstract: The leaf of a deciduous species completes its life cycle in a few months. During leaf maturation, osmolyte accumulation leads to a significant reduction of the turgor loss point (Ψ TLP ), a known marker for stomatal closure. Here we exposed two grapevine cultivars to drought at three different times during the growing season to explore if the seasonal decrease in leaf Ψ TLP influences the stomatal response to drought. The results showed a significant seasonal shift in the response of stomatal conductance to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 73 publications
4
15
0
Order By: Relevance
“…In agreement with past studies of grapevines, we observed an increase in foliar osmotic concentration in response to water deficit (Patakaset al , 2002;Hochberg et al , 2017) and as the seasonal progressed (Alsina et al , 2007;Sorek et al , 2021;Herrera et al , 2022). However, SC did not play a major role in these adjustments.…”
Section: Nscs Do Not Take Part In Grapevine Osmotic Adjustmentsupporting
confidence: 92%
“…In agreement with past studies of grapevines, we observed an increase in foliar osmotic concentration in response to water deficit (Patakaset al , 2002;Hochberg et al , 2017) and as the seasonal progressed (Alsina et al , 2007;Sorek et al , 2021;Herrera et al , 2022). However, SC did not play a major role in these adjustments.…”
Section: Nscs Do Not Take Part In Grapevine Osmotic Adjustmentsupporting
confidence: 92%
“…Such is the case of the turgor loss point (Ψ TLP ). Since Ψ TLP is coupled to stomatal closure (Brodribb et al, 2003 ), its adjustment to a lower Ψ x (a.k.a., osmotic adjustment) along the season (Bartlett et al, 2014 ; Herrera et al, 2022 ) allows plants to maintain transpiration in the face of declining Ψ x as the summer intensifies (Kozlowski & Pallardy, 2002 ). Adjusting the threshold of stomatal closure without changing the P 12 or P 50 seems unreasonable, as it would increase the risk of hydraulic failure and leaf death.…”
Section: Introductionmentioning
confidence: 99%
“…RWC is a factor that assesses both the effect of the soil−plant−atmosphere water continuum and the effect of membrane osmotic potentials. Indeed, different cultivars (but plants of the same species) with the same foliar water potential can have different RWCs [6]. RWC decreases proportionally with the decrease in water availability [7].…”
Section: Introductionmentioning
confidence: 99%